1980
DOI: 10.1095/biolreprod23.3.606
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Clearance Rate of Inhibin in Mature and Immature Male Rats

Abstract: The half-life and metabolic clearance rate of human seminal plasma inhibin after injection into male rats was studied. Labeled inhibin was injected i.v. into 27-day-old rats (10 ng, 3.5 X i0 cpm)and 75-day-old rats (15 ng, 5.5 X i0 cpm). In both age groups, rats were killed at intervals between

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1982
1982
1988
1988

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Furthermore, there was no correlation between the bioactivity of the inhibin preparations and the activity shown in radioreceptor displacement studies. Although radioreceptor assays for seminal plasma inhibin have been described (Vanage, Thakur, Kadam & Sheth, 1980;Sairam, Ranganathan, Ramasharma & Lamothe, 1981), they lack credibility on the basis of inadequate validation according to the criteria adopted by . An interesting feature of our studies was the strategy of screening large numbers of hybridomas secreting specific antibodies against inhibin.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there was no correlation between the bioactivity of the inhibin preparations and the activity shown in radioreceptor displacement studies. Although radioreceptor assays for seminal plasma inhibin have been described (Vanage, Thakur, Kadam & Sheth, 1980;Sairam, Ranganathan, Ramasharma & Lamothe, 1981), they lack credibility on the basis of inadequate validation according to the criteria adopted by . An interesting feature of our studies was the strategy of screening large numbers of hybridomas secreting specific antibodies against inhibin.…”
Section: Discussionmentioning
confidence: 99%
“…When testicular fragments from immature (42 day) rats were incubated in vitro for 3 hours with different inhibin preparations in the presence of 3 H-thymidine, incorporation of the label into testicular DNA was significantly inhibited. 57 Also, administration of inhibin to normal or hypophysectomized 42-day-old rats showed suppression of thymidine incorporation into testicular but not liver DNA. Autoradiographic study indicated that this effect was restricted to the germ cells, particularly type B spermatogonia.…”
Section: Testismentioning
confidence: 93%
“…Inhibin binds to anterior pituitary in vitro [44][45][46]57 and in vivo. 57 In analogy to other peptide hormones, the binding is presumably to specific plasma membranes receptors in the target cell. This assumption is strengthened by a good correlation between the binding and biologic activity of inhibin in vitro.…”
Section: Mechanism Of Actionmentioning
confidence: 99%
See 1 more Smart Citation